Photocatalytic Activity of TiO2-WO3 Composites - Beata Tryba; Michał Piszcz; Antoni W. Morawski (International Journal of Photoenergy)
TiO2-WO3 photocatalysts were prepared in a vacuum evaporator by impregnation of TiO2 with WO2 dissolved in an H2O2 solution (30%) and followed by calcination at 400 and 600∘C. XRD analyses showed that at 400∘C monoclinic phase of WO3 was dominated whereas at 600∘C both monoclinic and regular phases of WO3 were present. Modification of TiO2 by WO3 caused increasing in the absorption of light to the visible range. TiO2 and photocatalysts modified with low amount of WO3 (1–5 wt.%) showed high adsorption of Acid Red (AR) on their surface and enhanced photocatalytic activity under UV irradiation. Under visible light irradiation, TiO2-WO3 photocatalysts prepared at 400∘C were more active for AR decomposition than those prepared at 600∘C suggesting that monoclinic phase of WO3 is more active under visible light than regular WO3. Although TiO2-WO3 photocatalysts appeared to be active under visible light for decomposition of AR, the UV irradiation was more efficient.